An annotated checklist of Lithobiomorpha of China - Ma, Huiqin; Pei, Sujian; Hou, Xiaojie; Zhu, Tiegang; Wu, Dayong; Gai, Yonghua (Zootaxa, 2014)
The lithobiomorph centipede fauna of China is listed here based on literature data. A total of 68 species in 15 genera/subgenera in 2 families, Henicopidae and Lithobiidae, has been recorded from China. Three genera and forty-four species are known only from China, including the monotypic genera Pterygotergum and Hedinobius. The original descriptions of 16 nominal species were based on specimens of single sex only and 13 nominal species of Lithobius have never been allocated to a subgenus. Lithobius (Lithobius) zhui Pei, Ma, Shi, Wu & Gai, 2011 is moved to subgenus Lithobius (Ezembius). Distribution data for each species is provided here to promote further studies on the Lithobiomorpha fauna of China.